AN AUDIT OF MORBIDITY AND MORTALITY OF HOSPITALISED NEONATES IN NEONATAL CARE UNIT OF A TERTIARY CARE HOSPITAL IN ABBOTTABAD - Rehman, Anis -ur-; Qureshi, Azhar Munir; Najeeb, Shehzad; Siddiqui, Tahir Saeed; Idris, Muhammad; Ahmad, Tausif (Journal of Ayub Medical College Abbottabad, 2011)
Background: Perinatal as well as neonatal mortality record in our country is one of the highest in the world. Home deliveries, lack of adequate facilities, poverty and lack of education are some of the important known causes. The present study was planned to determine neonatal mortality in Hazara. Methods: Hospital records of neonatal admissions at Ayub Teaching Hospital (ATH) Abbottabad from 1st January 2007-31st December 2007 were analysed retrospectively. Percent neonatal mortality was calculated from the record, along with the causes of neonatal mortality. Results: A total of 1705 neonates were admitted in the study period at the department of neonatology Ayub Teaching Hospital Abbottabad. Out of 1,705 neonates 947 (56%) were males while 857 (44%) were females with a male to female ratio of 1.24:1. Majority, 1,411 out of 1,705 (83%), of the neonates was admitted during the 1st week of their life, mean age 6 days. Asphyxia, sepsis and prematurity were the three most common causes of neonatal admissions contributing 27%, 26% and 24% respectively. Overall mortality was 11%. Conclusion: Neonatal mortality is an important contributing factor to infant mortality in Hazara Division. Majority of patients was admitted in the first week of life which indicates that good antenatal and natal care can reduce the mortality and morbidity of our neonates. Improvement in the prenatal, natal and nursery care as a whole can reduce the neonatal mortality in preterm as well as full term neonates. Keywords: Neonatal Mortality, Morbidity, Asphyxia